Pengembangan Sistem Informasi Pendataan Rak dan Perangkat Server Berbasis Web (Studi Kasus Pada PT. Indosat Ooredoo Surabaya) - Dinda Ayu Rudyana Putri; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. Indosat Ooredoo is one of the telecommunications service providers in Indonesia. To support the smooth running of services, of course, better management of server space is needed. Servers that can be submitted are a very vital part of telecommunication network activity. In the Engineering Division, there are several problems that occur in the business process at PT. Surabaya Indosat Ooredoo. One of them, the Engineering Division does not yet have the resources that are capable of managing the server properly. Data collection activities on each rack and server device still use manual techniques using Microsoft Word and the Sketchup application. Based on the description of the importance above, it is necessary to improve the data collection business processes and device servers and by building a data collection information system and server devices. To develop an information system, the researcher uses one method, namely the Waterfall Model. In the Waterfall Model method 4 phase definitions, systems and software design are needed, implementation and unit testing and integration and unit testing. In the requirements analysis until the design of the researcher uses the Object Oriented Design and Analysis (OOAD) method to overcome errors in determining the user needs needed by the system. After the requirements analysis and design are carried out next, testing on the implementation of information systems rack data collection and server devices using functional and nonfunctional testing. On functional testing using a validation test with 18 functional requirements with results, 100% valid and nonfunctional tests using the browser compatibility validation test using SortSite software. The reported test results have 2 critical problems in Firefox browser version 63 and chrome version 70.